Hadena ligata Möschler (Lepidoptera: Noctuidae): distribution and revised taxonomy - Mccabe, Timothy L. (Zootaxa, 2003)
Hadena ligata Möschler, 1891 represents a previously unrecognized species of Dypterygia Stephens, 1829. This species was originally described from Puerto Rico and was collected in Florida. The adult habitus and the male and female genitalia are illustrated, and a lectotype is designated. The larvae of Dypterygia rozmani Berio, 1974 and Trachea delicata (Grote, 1874) are illustrated.